Health impact assessment, human rights and global public policy: a critical appraisal - Alex Scott-Samuel; Eileen O'Keefe (The World Health Organization, 2007)
Public policy decisions in both the social and economic spheres have enormous impact on global public health. As a result of this, and of the skewed global distribution of power and resources, health impact assessment (HIA) potentially has a key role to play in foreign policy-making and global public policy-making. Governments, multilateral bodies and transnational corporations need to be held to account for the health impacts of their policies and practices. One route towards achieving this objective involves the inclusion of human rights assessments within HIA. International commitments to human rights instruments and standards can be used as a global auditing tool. Methodological issues may limit the effectiveness of HIA in promoting health equity. These issues include the use of procedures that favour those holding power in the policy process or the use of procedures that fail to apply values of equity and participation. The identification and production of evidence that includes the interests of less powerful groups is a priority for HIA and would be furthered if a human rights-based method of HIA were developed. Because HIA considers all types of policies and examines all potential determinants of health, it can play a part when foreign policy is developed and global decisions are made to treat people as rights holders. Since the human right to health is shaped by the determinants of health, developing links between the right to health assessment (that is, an assessment of the impact of policies on the right to health) and HIA - as recently proposed by the United Nations Special Rapporteur on the right to health - could strengthen the development of foreign policy and global decisions. Such links should be pursued and applied to the development of foreign policy and to the operation of multilateral bodies.